Application of instrumented paddles in measuring on-water kinetics of front and back paddlers in K2 sprint kayaking crews of various ability levels - Kong, P. W.; Tay, C. S.; Pan, J. W. (Sensors, 2020)
This study used instrumented paddles to obtain on-water kinetic variables of two-seater (K2) crews during sprint kayaking. A total of 74 male kayakers of various ability levels (national team: 9, recreational club: 38, school team: 27) comprising 39 K2 crews were recruited. Both the front and back paddlers were provided with an instrumented paddle to perform 200-m maximal effort paddling in a reservoir. Force, power, and temporal variables were extracted from the paddle data. Difference among groups were compared using a factorial Analysis of Variance. Results showed that the force, power, and temporal characteristics of the front and back paddlers were similar during maximal effort sprint kayaking. Proficient kayakers produced greater kinetic outputs than less proficient kayakers, while the coordination strategy based on timing differences at key events between the two crew members in a K2 boat was similar across ability levels. These data can be useful for coaches, sport scientists, and athletes in planning and monitoring the training.